Effect of NAA and Zinc Sulphate on Marketable Yield and Physical Parameters of Litchi (Litchi chinensis Sonn.) cv. Rose Scented - , Anand Singh Rawat, V.K. Tripathi (Archives of Current Research International, 2024)
An experiment was conducted in the Garden, Department of Fruit Science at C.S. Azad University of Agriculture and Technology, Kanpur (U.P.) during two continuous years i.e., 2022 and 2023 to assess the effect of NAA (Naphthalene acetic acid) and zinc sulphate on marketable yield and physical parameters of litchi (Litchi chinensis Sonn.) cv. Rose Scented. For this experiment, sixteen treatments including four levels of each NAA (0, 25, 50, and 75 ppm) and zinc sulphate (0, 0.2, 0.4 and 0.6%), and their combinations were applied in Factorial-CRD with three replications. The foliar application of these treatments was done on January 28 and March 16’ 2022 and 2023, before flowering and again during fruit setting (pea stage). A carboxymethyl group substituted NAA (Naphthalene acetic acid) at position 1. It has a role as a synthetic auxin. It is a conjugate acid of a 1-naphthaleneacetate. 1-Naphthylacetic acid is a natural product found in Humulus lupulus, Rehmannia glutinosa, and other organisms. The results of the experiment clearly show that plants treated with NAA @ 50ppm and zinc sulphate @ 0.4% significantly increased yield of marketable fruits of 79.11 and 83.17 kg/plant, respectively during both years of investigations. Simultaneously, the highest fruit length (3.57 and 3.60 cm), fruit diameter (3.22 and 3.20 cm) and fruit weight (19.99 and 20.54 g) were also recorded which were produced from the plants treated with the combination of NAA @ 50 ppm and ZnSO4 @ 0.4%. This treatment (NAA @ 50 pm and ZnSO4 @ 0.4%) also gave blend results in respect to seed physiology with decreasing seed length (1.17 and 1.30 cm), seed diameter (1.23 and 1.25 cm) and produced minimum seed weight (3.34 and 3.37 g). The same treatment also showed a simultaneous increase in pulp weight (13.45 and 13.98 g) and pulp: seed ratio (4.02 and 4.08) with reduced rind weight (3.20 and 3.19 g) in litchi fruits in the north Indian plains.